OXIDATIVE AND NITROSATIVE DISTURBANCES IN THE RAT BRAIN FOLLOWING REPEATED MILD TRAUMATIC BRAIN INJURY - I.M. Adamovych; V.O. Kostenko (Проблеми екології та медицини)
The aim of this study was to determine the patterns of oxidative and nitrosative stress development in cerebral hemisphere homogenates of rats exposed to repeated mild traumatic brain injury (rmTBI). Materials and methods. The study was conducted on 28 male rats, divided into three groups: Group 1 (control) – intact animals; Group 2 – sham-injured rats, which underwent anesthesia and head fixation without trauma (five procedures at 48-hour intervals); and Group 3 – rats subjected to repeated mild traumatic brain injury (rmTBI), involving anesthesia, fixation, and impact-induced injury (five procedures at 48-hour intervals). rmTBI was modeled by applying an impact with a 49.5 g weight to the skull of rats under under inhalation anesthesia with sevoflurane. Spectrophotometric methods were used to evaluate the rate of superoxide anion radical production, the activity of various nitric oxide synthase (NOS) isoforms, and the levels of reactive nitrogen species, including nitrite ions, S-nitrosothiols, and 3-nitrotyrosine. Results. The study revealed that even sham injury led to a moderate increase in superoxide anion radical production: by microsomes (+9.2%), by mitochondria (+19.6%), by leukocytes and glial cells (+42.6%). Endothelial NOS activity increased by 44%, S-nitrosothiol concentration decreased by 27.9%, and 3-nitrotyrosine content rose by 110.6%. Following rmTBI, a significant increase in superoxide production was observed relative to the sham-injured group: by microsomes (+16.2%), by mitochondria (+11.7%), by leukocytes and glial cells (+ 42.9%). In the sham-injured group, total NOS activity increased by 45.6%, mainly due to inducible NOS (+93.8%) and neuronal NOS (+27.8%), the levels of nitrites, S-nitrosothiols, and 3-nitrotyrosine rose by 72.5%, 47.7%, and 57.6%, respectively, indicating the development of pronounced oxidative and nitrosative stress and potential protein nitration in brain tissue after rmTBI. Conclusions. By day 14 following rmTBI, pronounced signs of oxidative and nitrosative stress were evident in the cerebral hemispheres of rats. Sham injury also led to moderate changes in oxidative imbalance markers. These findings highlight the potential of redox biomarkers as promising targets for neuroprotective interventions in the aftermath of rmTBI.